(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This research focuses on analyzing the quality of services provided by the Government’s Internal Supervision Apparatus for the Development of Tourism Villages in South Minahasa Regency. In this analysis, a framework of five service quality dimensions will be used to understand the service quality of internal supervisory officers including reliability, responsiveness, assurance, empathy and physical evidence. This research aims to determine the influence of reliability, responsiveness, assurance, empathy and physical evidence on the development of tourist villages in South Minahasa Regency. The population in this study was a tourist village in South Minahasa Regency. The sample used was 34 respondents. The research instrument used a questionnaire and was processed using the SPSS 27 program, with the method used being multiple linear regression analysis. The results of the research statistically provide the conclusion that the reliability, assurance, empathy and physical evidence of Government Internal Supervisory Apparatus together influence the development of tourist villages in South Minahasa Regency. However, partially, the responsiveness of the Government Internal Supervisory Apparatus has no influence on the development of tourist villages in South Minahasa Regency.